Real-time monitoring and data acquisition using LoRa for a remote solar powered oil well - Chidolue, Onyinyechukwu; Iqbal, Tariq (International Journal of Applied Power Engineering (IJAPE), 2024)
Real-time monitoring is essential for solar-powered systems as they can be affected by sudden environmental changes, which may occur unpredictably, especially in isolated regions. This study proposes a wireless communication-based approach that allows for data acquisition and system monitoring of the entire solar system of a remote oil well. The proposed instrumentation method offers an affordable solution for monitoring the battery voltage, photovoltaic (PV) current, the converter's alternating current (AC), and oil well management. A wireless communication tool for a long-range called LoRa is used, with the TTGO LoRa32 SX1276 organic light-emitting diode (OLED) as the sender node and Heltec long range (LoRa) ESP 32 as the transmitter node. These I.C.s are ESP32 development boards with an integrated LoRa chip and an SSD1306 flash memory. System design and some test results are included in the paper.